Who am I? Who do you think I am? Stability of racial/ethnic self-identification among youth in foster care and concordance with agency categorization. (September 2015) - Schmidt, Jessica; Dubey, Shanti; Dalton, Larry; Nelson, May; Lee, Junghee; Oberweiser Kennedy, Molly; Kim-Gervey, Connie; Powers, Laurie; Geenen, Sarah
Abstract: While it has been well documented that racial and ethnic disparities exist for children of color in child welfare, the accuracy of the race and ethnicity information collected by agencies has not been examined, nor has the concordance of this information with youth self-report. This article addresses a major gap in the literature by examining 1) the racial and ethnic self-identification of youth in foster care, and the rate of agreement with child welfare and school categorizations; 2) the level of concordance between different agencies (school and child welfare); and 3) the stability of racial and ethnic self-identification among youth in foster care over time. Results reveal that almost 1 in 5 youth change their racial identification over a one-year period, high rates of discordance exist between the youth self-report of Native American, Hispanic and multiracial youth and how agencies categorize them, and a greater tendency for the child welfare system to classify a youth as White, as compared to school and youth themselves. Information from the study could be used to guide agencies towards a more youth-centered and flexible approach in regard to identifying, reporting and affirming youth's evolving racial and ethnic identity. Highlights: Examined stability of racial/ethnic self-identification among adolescents in foster care Compared youth self-report with agency categorizations of race/ethnicity Found especially high rates of agency-youth discordance for certain groups of youth Child welfare system more likely to classify youth as White compared to school and youth themselves